2014
DOI: 10.1074/jbc.m113.543033
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Proton-transfer Step in the Cofactor-free (1H)-3-Hydroxy-4-oxoquinaldine 2,4-Dioxygenase

Abstract: Background: The mechanism of cofactor-free dioxygenases has not been clearly elucidated.Results: Mutation of the His/Asp dyad in (1H)-3-hydroxy-4-oxoquinaldine 2,4-dioxygenase strongly affects substrate deprotonation and overall catalysis.Conclusion: Base mechanism is demonstrated where His-251 acts as catalytic base and Asp-126 modulates basicity.Significance: Many dioxygenases activate their substrates via deprotonation, which is an essential step for later reaction with oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 53 publications
3
45
1
1
Order By: Relevance
“…Analysis of the three-dimensional structure of Hod and the biochemical data of His251Ala Hodmuteins showed that His251 is the catalytically active base that accepts a proton from the substrate. The formed substrate anion then reacts with molecular oxygen without the need for a metal or a cofactor (29)(30)(31). Hod was partially inhibited by imidazole (as Lcp) in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Analysis of the three-dimensional structure of Hod and the biochemical data of His251Ala Hodmuteins showed that His251 is the catalytically active base that accepts a proton from the substrate. The formed substrate anion then reacts with molecular oxygen without the need for a metal or a cofactor (29)(30)(31). Hod was partially inhibited by imidazole (as Lcp) in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 95%
“…Hod was partially inhibited by imidazole (as Lcp) in a concentration-dependent manner. However, the mechanism of inhibition remained unknown (29). Interestingly, Lcp proteins of different species have two conserved His residues (His198 and His203 in Lcp of Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…To keep the computations tractable most of the surrounding aminoacids were excised, and only the Asp-His dyad responsible for the initial deprotonation of substrate (Steiner et al, 2010; Hernandez-Ortega et al, 2014) and charge stabilization of the 3 I 1 / 1 I 1 intermediates was kept. Table 1 shows that this truncation has very modest effects on the reaction energetics, and should therefore not introduce relevant errors.…”
Section: Resultsmentioning
confidence: 99%
“…As in previous work by Hernandez-Ortega et al (2014), all computations were repeated for four different (1 H )-3-hydroxy-4-oxoquinolines to ascertain the influence of different substituents (methyl, pentyl, fluor and nitro) in the reaction course. The minimum-energy crossing points found (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the enzyme 1-H-3-hydroxy-4-oxoquinaldine 2,4-dioxygenase performs an intradiol-type dioxygenation of an aromatic substrate in the absence of co-factor although the reaction is slow. 15,16 Therefore, co-factors, such as transition metals in metalloenzymes, are expected to speed up biochemical reactions significantly by lowering the rate determining energy barrier in a reaction mechanism. Metalloenzymes can be mononuclear or binuclear or contain more than two metal centers, 17 however, in this review we will focus on mononuclear iron complexes only.…”
Section: Introductionmentioning
confidence: 99%